A solution design and test case for invoice generation system in operational dynamic Telco industry - Ahmad, Mohd Ridzam; Abdul Wahad, Ahairul Afza; Koh, Tieng Wei; Sharif, Khaironi Yatim (2014)
An Invoice Generator system helps the Telco Company to accelerate invoice generation for customer billing purposes. However, companies face difficulty to perform test on the Invoice Generator system with the rapid changes of Billing and Rating plan over time. Since the ERP and CRM systems are central to the functioning of the Telco Company, it is important to not disrupt these systems in the process of performing better output for the invoice statement. Thus, a proper technique, design and test cases required for the company to execute the software testing. Finally, the company could use the design solution described in this study to minimize errors in invoice productions.